Determinants of Oil Palm Production (Case Study in Pauhranap Village, Peranap District, Indragiri Hulu Regency) - Gukguk, Mangatur Raja; Harahap, Gustami (CV. Publikasi Indonesia, 2025)
This study examines the factors influencing oil palm production in Pauhranap Village, Peranap District, Indragiri Hulu Regency. Using a quantitative approach, data were collected from 45 farmers and analyzed using multiple linear regression. The results indicate that fertilizer use and the number of seedlings have a significant positive effect on oil palm production, while land area does not show a significant impact. Pesticide use also contributes positively to production but to a lesser extent. Based on these findings, recommendations include the adoption of precision fertilization techniques, ideal planting density management, and the use of environmentally friendly bio-pesticides. Additionally, local governments should enhance extension programs and promote modern agricultural technology adoption. This study provides insights for policymakers, farmers, and academics to improve oil palm productivity sustainably.